Influence of different concentrations of titanium dioxide and copper oxide nanoparticles on water sorption and solubility of heat‐cured PMMA denture base resin - Rashin Giti; Maryam Firouzmandi; Neda Zare Khafri; Elham Ansarifard (Wiley, 2022)
Abstract Objectives This study aimed to evaluate the effect of different concentrations of titanium dioxide (TiO2) and copper oxide (CuO) nanoparticles on the water sorption and solubility of heat‐cured polymethyl methacrylate (PMMA). Materials and Methods Fifty disc‐shaped specimens (10 × 2 mm) of heat‐cured PMMA were prepared and divided into five groups (n = 10) to be modified with 2.5 wt.% or 7.5 wt.% of either TiO2 or CuO nanoparticles. One group was left unmodified, serving as the control group. Water sorption and solubility were measured by weighing the specimens before and after immersion in distilled water and desiccation. The data were analyzed by using one‐way ANOVA and Tukey's post hoc test (α = .05). Results The 2.5 wt.% CuO nanoparticles significantly decreased the water sorption (p = .016), but did not change the water solubility (p = .222) compared with the control group. The 7.5 wt.% CuO and both concentration of TiO2 nanoparticles did not change the water sorption, but significantly increased the solubility of heat‐cured PMMA (p ≤ .05). Conclusion Adding 2.5 wt.% CuO nanoparticles to heat‐cured PMMA decreases the water sorption; although, it has no significant effect on the solubility. Likewise, 2.5 and 7.5 wt.% TiO2 and 7.5 wt.% CuO do not affect the water sorption, but increase the water solubility of heat‐cured PMMA. Clinical Significance Reinforcing the heat‐cured PMMA denture base resin materials with the right concentration and type of nanoparticles can decrease the water sorption of resin base materials, and consequently can influence the durability of dentures.